2004
DOI: 10.2337/diabetes.53.2007.s166
|View full text |Cite
|
Sign up to set email alerts
|

Acute ω-3 Fatty Acid Enrichment Selectively Reverses High-Saturated Fat Feeding-Induced Insulin Hypersecretion But Does Not Improve Peripheral Insulin Resistance

Abstract: In rats fed a high-saturated fat diet, replacement of a small percentage of total fatty acids with long-chain -3 fatty acids from fish oil for the duration of high-fat feeding prevents the development of insulin resistance. We investigated the effect of acute (24-h) modulation of dietary fat composition on glucose-stimulated insulin secretion (GSIS) in rats made insulin resistant by highsaturated fat feeding for 4 weeks. Insulin secretion after an intravenous glucose challenge was greatly increased by high-sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 25 publications
1
19
1
2
Order By: Relevance
“…Although we also found an increased postprandial insulin response with palmitic acid compared with oleic acid, our observation of higher insulin response to linoleic acid than to oleic acid is not consistent with the data of Stein et al (34). Holness et al (35) reported that acute replacement of some dietary saturated fatty acids with EPA and DHA, in rats made insulin resistant by high-saturated fat feeding for 4 weeks, reversed insulin hypersecretion in vivo and during glucose perifusion of isolated islets. The lowered insulin secretion, however, was not accompanied by improved insulin action, and glucose tolerance was adversely affected.…”
Section: Methodscontrasting
confidence: 98%
“…Although we also found an increased postprandial insulin response with palmitic acid compared with oleic acid, our observation of higher insulin response to linoleic acid than to oleic acid is not consistent with the data of Stein et al (34). Holness et al (35) reported that acute replacement of some dietary saturated fatty acids with EPA and DHA, in rats made insulin resistant by high-saturated fat feeding for 4 weeks, reversed insulin hypersecretion in vivo and during glucose perifusion of isolated islets. The lowered insulin secretion, however, was not accompanied by improved insulin action, and glucose tolerance was adversely affected.…”
Section: Methodscontrasting
confidence: 98%
“…As such, SFA-rich diets, when compared with polyunsaturated fatty acid diets, are known to cause glucose intolerance and to increase insulin resistance [2]. Additionally, previous studies reported that the consumption of SFA had an insulinogenic effect [13,24]. This effect appears to be related to the increase in intracellular calcium concentration in the pancreatic islets, which consequently augmented the insulin release [45].…”
Section: Discussionmentioning
confidence: 90%
“…This "repartitioning" contributed to their rather beneficial effects, such as reduction of blood serum levels of VLDL, triacylglycerols, and cholesterol and decrease of insulin resistance (de Lorgeril and Salen, 2006). Other positive treatment effect of n-3 PUFAs has been related to their interference with insulinotropic effects of saturated fatty acids, lowering insulin-dependent stimulation of lipogenic genes in the liver (Holness et al, 2004). PUFA-mediated activation of PPAR␣ was demonstrated to antagonize detrimental effects on pancreatic ␤-cells in vitro, being able to rescue ␤-cell function (Holness et al, 2007) and advantageous effects of PUFA supplementation in steatosis were suggested to result from an improvement of peripheral insulin resistance, which was demonstrated in vitro but not supported by findings in vivo (Fickova et al, 1998;Ryan et al, 2000;Holness et al, 2004).…”
Section: Therapeutic Effects Of Polyunsaturated Fatty Acids In Nonalcmentioning
confidence: 99%
“…Other positive treatment effect of n-3 PUFAs has been related to their interference with insulinotropic effects of saturated fatty acids, lowering insulin-dependent stimulation of lipogenic genes in the liver (Holness et al, 2004). PUFA-mediated activation of PPAR␣ was demonstrated to antagonize detrimental effects on pancreatic ␤-cells in vitro, being able to rescue ␤-cell function (Holness et al, 2007) and advantageous effects of PUFA supplementation in steatosis were suggested to result from an improvement of peripheral insulin resistance, which was demonstrated in vitro but not supported by findings in vivo (Fickova et al, 1998;Ryan et al, 2000;Holness et al, 2004). Finally, another putative protection mechanism of unsaturated fatty acids in steatosis and steatohepatitis was attributed to their antioxidant effects, serving as a cellular reservoir for undue lipid peroxidation (Davis et al, 2006;Oliveira et al, 2006).…”
Section: Therapeutic Effects Of Polyunsaturated Fatty Acids In Nonalcmentioning
confidence: 99%